Neonatal post-hemorrhagic hydrocephalus resulting in foraminal septae-radiological technique and surgical implications - Fadzli, F.; Ramli, N.M.; Rahmat, K.; Ganesan, D. (Springer, 2013)
Intraventricular haemorrhage is the most common cause of hydrocephalus in a pre-term baby and may require surgical intervention depending on severity. This case illustrates foraminal septae as a subtle cause of progressive quadriventricular hydrocephalus in a child born pre-term with a history of grade III intraventricular haemorrhage. The septae within the fourth ventricular exits were clearly demonstrated with 3D-FIESTA (fast imaging employing steady-state acquisition) MRI acquisitions and assisted in differentiation from communicating hydrocephalus. This finding guided the decision to a successful endoscopic third ventriculostomy. 3D-FIESTA sequence is recommended for investigating children with hydrocephalus secondary to intraventricular haemorrhage due to its diagnostic potential and implications on surgical technique.